The small HDL particle hypothesis of Alzheimer's disease. Issue 2 (13th April 2022) - Martinez, Ashley E.; Weissberger, Gali; Kuklenyik, Zsuzsanna; He, Xulei; Meuret, Cristiana; Parekh, Trusha; Rees, Jon C.; Parks, Bryan A.; Gardner, Michael S.; King, Sarah M.; Collier, Timothy S.; Harrington, Michael G.; et al.
Abstract: We propose the hypothesis that small high‐density lipoprotein (HDL) particles reduce the risk of Alzheimer's disease (AD) by virtue of their capacity to exchange lipids, affecting neuronal membrane composition and vascular and synaptic functions. Concentrations of small HDLs in cerebrospinal fluid (CSF) and plasma were measured in 180 individuals ≥60 years of age using ion mobility methodology. Small HDL concentrations in CSF were positively associated with performance in three domains of cognitive function independent of apolipoprotein E ( APOE ) ε4 status, age, sex, and years of education. Moreover, there was a significant correlation between levels of small HDLs in CSF and plasma. Further studies will be aimed at determining whether specific components of small HDL exchange across the blood, brain, and CSF barriers, and developing approaches to exploit small HDLs for therapeutic purposes.